Effect of feeding rapeseed-mustard cake during pregnancy on the performance of ewes - Dutta, Narayan; Sharma, K; Singh, M; Singh, A (The Indian Journal of Animal Sciences, 2012)
This study examined the effect of feeding high glucosinolate rapeseed-mustard cake (RMC) on the performance of ewes during pregnancy. Sixteen Muzaffarnagari ewes (28.9± 1.1 kg) were teased twice daily for oestrus detection and bred by single ram during standing oestrus. Ewes returning to heat again in the subsequent cycle were re-bred. Confirmed pregnant ewes (12) were divided randomly into 2 equal groups and allocated to 1 of the dietary treatment GNC or RMC, concentrate mixture containing groundnut cake (GNC) or RMC as major protein source was fed to respective animal group. The glucosinolates (Gls) content in RMC supplement was 30.75µmol/g. All the ewes were offered wheat straw ad lib. as basal roughage along with required amount of respective concentrate mixtures to meet their nutrients requirement for maintenance and pregnancy. Two metabolism trials were conducted, during early and late gestation. Supplementation of RMC to wheat straw based diet reduced the total DMI by gravid ewes but digestibility coefficient of various nutrients was comparable between both treatments. The digestible nutrient intake and nutritive value of diets during late pregnancy was reduced in RMC group. Net retention of N (g/d), per cent of intake or per cent of absorbed N was significantly lower in RMC fed gravid ewes during early and late gestation. All the gravid ewes gained weight throughout gestation period, however, gross gain after 21 weeks and net gain was lower in RMC fed animals. Blood-biochemical attributes (haemoglobin, PCV, glucose, serum proteins, urea, calcium and phosphorus, AST and ALT levels) did not differ significantly between RMC and GNC fed animals. Serum T3 (triiodothyronine) did not differ significantly irrespective of dietary treatments, while, concentration of T4 (tetra iodothyronine) hormone was significantly lower in RMC fed animals. It may be concluded that the feeding of RMC (41% in concentrate mixture) significantly reduced the palatability of concentrate, gross gain after 21 weeks of pregnancy, net gain and thyroxine concentration in blood of gravid ewes.